2009
DOI: 10.1088/0953-4075/42/22/225402
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of wakefield intensity

Abstract: We report on the measurement of the wakefield of an ion moving through a beam–foil plasma using an indirect experimental method. The standard beam–foil time-of-flight technique is used to measure the lifetime of the perturbed H-like V 2s2S1/2 state due to its passage through the wakefield. This measured lifetime along with the theoretical lifetimes of pure H-like V 2s2S1/2 and 2p2P1/2 states has been used to determine the Stark mixing parameter of H-like 2s2S1/2 and 2p2P1/2 states, which is further exploited t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
7
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 25 publications
1
7
0
Order By: Relevance
“…Since the exit wakefield for the metal part is predicted to be larger than that for polypropylene or PET (a nonconductor), we propose that the differential energy loss as well as the differential straggling is due to this exit wake field. These measurements reveal wake-field-induced Stark mixing of the substates in a solid [9,10]. Hence, we tentatively ascribe this extra differential energy loss to the stronger metal exit wake field.…”
mentioning
confidence: 57%
See 1 more Smart Citation
“…Since the exit wakefield for the metal part is predicted to be larger than that for polypropylene or PET (a nonconductor), we propose that the differential energy loss as well as the differential straggling is due to this exit wake field. These measurements reveal wake-field-induced Stark mixing of the substates in a solid [9,10]. Hence, we tentatively ascribe this extra differential energy loss to the stronger metal exit wake field.…”
mentioning
confidence: 57%
“…Segregating the contributions of the two surfaces from the bulk has not yet been possible. However, many years ago, bulk wake-field-induced Stark mixing of the sub states in H-like Kr ions [9] and recently the surface wake field intensity [10] in carbon foils have been measured. The latter showed that small surface wake field can be distinguished from the large bulk energy loss field in an atomic level lifetime measurement [10].…”
mentioning
confidence: 99%
“…Therefore, no target ionization is possible by electron capture processes, however, target ionization by direct ionization process will take place equally by all the charge species. The contribution of energy loss from direct ionization can be obtained from As mentioned already that surface wakefield gave rise to energy loss at the surface [3] and the energy loss due to surface wakefield varies with charge state. Further, we discussed above that nearly neutral atoms emerge out from the exit surface irrespective of the difference in charge state at the incidence.…”
Section: Resultsmentioning
confidence: 99%
“…Long ago Ritchie [2] suggested with the basis of surface plasmon theory that a fast electron moving through a foil would lose its energy to both bulk as well as surface. Nevertheless only recently, our experiment [3] showed that stopping power of swift ions through solids can also distinguish these two contributions clearly. Surface stopping power is determined to be only a two order of magnitude smaller than that of the bulk stopping power of the 3.1 MeV/u vanadium ion beam passing through a carbon foil.…”
Section: Introductionmentioning
confidence: 80%
See 1 more Smart Citation